ANALISIS MANUVER PENYELAMATAN SATELIT PALAPA - D - Triharjanto, Robertus Heru; Hutasulut, Hagorly M (Indonesian Journal of Aerospace, 2010)
The paper discusses the analysis on orbit maneuver done to rescue PALAPA-D satellite stranded in high elliptical orbit during its launch in 2009. The purpose of the research is as an exercise for LAPAN and ITB on designing orbit maneuver, especially in the rescue of satellite stranded while approaching its GTO during its launch. The study will gain knowledge on the key factors that make the rescue effort successful. The simulation is done using orbit analysis software STK. Meanwhile, the LM-3 launcher and Spacebus-4000 satellite bus data is taken from internet publication. The result on the life of the satellite is only difference by 1,9% from the one calculated by the satellite manufacturers, Thales Alenia. Therefore, it can be concluded that the analysis has good validity.